Mapping the recognition domains of pneumococcal fibronectin‐binding proteins PavA and PavB demonstrates a common pattern of molecular interactions with fibronectin type III repeats. Issue 6 (7th July 2017) - Kanwal, Sajida; Jensch, Inga; Palm, Gottfried J.; Brönstrup, Mark; Rohde, Manfred; Kohler, Thomas P.; Somplatzki, Daniela; Tegge, Werner; Jenkinson, Howard F.; Hammerschmidt, Sven
Summary: Colonization of mucosal respiratory surfaces is a prerequisite for the human pathobiont Streptococcus pneumoniae (the pneumococcus) to cause severe invasive infections. The arsenal of pneumococcal adhesins interacts with a multitude of extracellular matrix proteins. A paradigm for pneumococci is their interaction with the adhesive glycoprotein fibronectin, which facilitates bacterial adherence to host cells. Here, we deciphered the molecular interaction between fibronectin and pneumococcal fibronectin‐binding proteins (FnBPs) PavA and PavB respectively. We show in adherence and binding studies that the pneumococcal interaction with fibronectin is a non‐human specific trait. PavA and PavB target at least 13 out of 15 type III fibronectin domains as demonstrated in ligand overlay assays, surface plasmon resonance studies and SPOT peptide arrays. Strikingly, both pneumococcal FnBPs recognize similar peptides in targeted type III repeats. Structural comparisons revealed that the targeted type III repeat epitopes cluster on the inner strands of both β‐sheets forming the fibronectin domains. Importantly, synthetic peptides of FnIII 1, FnIII 5 or FnIII 15 bind directly to FnBPs PavA and PavB respectively. In conclusion, our study suggests a common pattern of molecular interactions between pneumococcal FnBPs and fibronectin. The specific epitopes recognized in this study can potentially be tested as antimicrobial targets in further scientific endeavours. Abstract : Streptococcus pneumoniae interacts with the C‐terminal part of fibronectin consisting of 15 FnIII repeats. The adhesins PavA and PavB interact with most of the FnIII repeats and, strikingly, target similar sequence motifs, suggesting a common pattern of interactions between Fn and pneumococcal adhesins. The PavA and PavB FnIII motifs may therefore be employed as potential antimicrobials to combat pneumococcal colonization.